Future public policy and its knowledge base: shaping worldviews through counterfactual world-making. Issue 2 (2nd April 2020) - Hillgren, Per-Anders; Light, Ann; Strange, Michael
Abstract: Research in diverse areas such as climate change, happiness and wellbeing emphasizes the need for transformative change, stressing the importance of rethinking established values, goals and paradigms prevailing among civil servants, policy- and decision makers. In this paper, we discuss a role that design can play in this, especially how processes of counterfactual world-making can help facilitate reflection on worldviews and the shape of future forms of governance. By exploring different presents, rather than conditions in the future, this approach allows civil servants to consider, create and resist playful alternatives to business-as-usual. In this way, we demonstrate how design can stimulate imagination both as to futures and people's role in shaping these futures.